Highway & Expressway: Kathmandu Terai Fast Track & Its Multidimensional Impact in Shaping the Future of Nepal - Chaudhary, Sumit; Pokharel, Uzwal; Adhikari, Sabin (KTFT Journal, 2024)
Kathmandu Terai Fast Track is prioritized as a national pride project, constructed by the Nepal army. It is supposed to revolutionize transportation in the country. The KTFT Expressway plays a vital role in the state-building process, particularly by reducing travel time and quality of road communication to the provincial capitals. The project can accelerate the country's economic growth, improve trade links, provide greater market access to the industry, and connect southern states to the capital of the country. The project has a new approach to constructing roads, tunnels, and tall sophisticated bridges that allows technocrats to sharpen their knowledge and improve their skill. The project is marked as the game changer for the Nepalese economy. The article through the research methodology tries to incorporate the multidimensional impacts that the expressway will have in shaping the future of Nepal.